The production of methacrylic acid in Escherichia coli - Yiakoumetti, Andrew (2016)
The global demand for methyl methacrylate, a derivative of methacrylic acid, exceeds 2 million tonnes per annum. Current production methods rely entirely upon crude oil and natural gas as feedstocks, use harsh conditions and generate hazardous waste, which has led to an increased demand for bio-derived Perspex. However, the lack of known metabolic pathways in which methyl methacrylate or methacrylic acid are intermediates has prevented Bio-Perspex from becoming a reality. Recently, the hydrolysis of methacrylyl-CoA, an intermediate of the valine degradation I pathway, was proposed as a candidate step for the biocatalytic production of methacrylic acid, but remained unsubstantiated. This project describes the whole-cell biocatalytic production of methacrylic acid via the hydrolysis of methacrylyl-CoA in both biotransformations of isobutyric acid and fermentations from glucose. To hydrolyse methacrylyl-CoA, thioesterases were screened for promiscuous activity on methacrylyl-CoA, and 4 hydroxybenzoyl-CoA thioesterase (4HBT) from Arthrobacter sp. strain SU was found to selectively hydrolyse methacrylyl-CoA over isobutyryl CoA (the precursor to methacrylyl-CoA). As this pathway is not naturally found in E. coli, the preferred host, the oxidation of isobutyryl-CoA to methacrylyl-CoA was engineered into the organism. This step is usually performed by acyl-CoA dehydrogenases, but as these require a complex mechanism for electron transfer to the organism’s electron transport chain, an acyl CoA oxidase, ACX4 from Arabidopsis thaliana, was used instead. The oxidation of isobutyryl-CoA was confirmed in vitro, as was the production of methacrylic acid from isobutyryl-CoA in an enzyme coupled reaction between 4HBT and ACX4. For the biotransformation of isobutyric acid to methacrylic acid, 4HBT, ACX4 as well as an acyl-CoA synthetase, AcsA from Pseudomonas chlororaphis B23 were co-expressed in E. coli. Cultures supplemented with isobutyric acid produced 367±28 μM methacrylic acid in minimal medium. For the production of methacrylic acid from glucose, branched chain keto acid dehydrogenases from Pseudomonas putida KT2440 and Bacillus subtilis 168 were co-expressed with 4HBT and ACX4. The strain with the branched chain keto acid dehydrogenase from P. putida produced 171 ± 7.6 μM methacrylic acid, also in a minimal medium. Overexpressing enzymes for the upregulation of 2-ketoisovalerate actually reduced MAA production, but also led to the production of 13mM isobutyric acid in a complex medium, suggesting a bottleneck in the pathway and the background hydrolysis of isobutyryl-CoA. The optimisation of gene expression and the disruption of enzymes that non-productively consume pathway intermediates is proposed, as is the testing of alternative routes to isobutyryl-CoA and the use of a host organism which naturally hosts the valine degradation I pathway.